Phraseographie - Hallsteinsdóttir, Erla (HERMES - Journal of Language and Communication in Business, 2006)
Multiword expressions – i.e. phraseological units – like idioms and collocations are one of the most interesting part of every language. In this article, I investigate phraseological units from a lexicographical point of view. I discuss the theoretical and methodological basis of phraseography as a discipline that includes aspects of lexicography, phraseology, corpus linguistics and theories of language learning. I demonstrate the importance of corpora as a source for the lexicographer and the use of corpus data. I also discuss the requirements for the lexicographical treatment of phraseological units by the compilation of a phraseological database for language learners in relation to their assumed needs that have already been described in detail.